Adaptation in a Changing World: Evolutionary mechanisms of salt tolerance in a coastal amphibian - Albecker, Molly (East Carolina University, 2018)
In order to predict evolutionary outcomes of environmental change on populations in nature, we need an improved understanding of the biological mechanisms that affect whether organisms will adapt to a changed environment. This dissertation capitalizes on the unlikely discovery of a freshwater treefrog (Hyla cinerea) inhabiting brackish marshes along the coast of North Carolina to better understand adaptive evolution to a changed environment. The goals of this research are to (1.) examine the extent that salt-exposed, coastal frog populations are diverging from salt-naïve, inland populations in response to saltwater exposure across life stages, (2.) determine the molecular and life history mechanisms that permit this species to persist in brackish habitats, and (3.) explore factors that influence likelihoods of evolution (e.g., density dependence, phenotypic plasticity). Chapter 1 used field surveys, meta-analysis, and common garden experiments to show that Hyla cinerea are unique among frog species in their ability to inhabit saline wetlands. Coastal H. cinerea laid more eggs in saltwater compared to inland H. cinerea, more coastal eggs hatched in saltwater compared to inland eggs, and in the highest experimental treatment (12ppt), early-stage coastal tadpoles had higher survival rates than inland tadpoles. Chapter 2 investigated the role of plasticity in generating divergent phenotypes across larval development. Regardless of salinity, coastal tadpoles grew faster and initiated metamorphosis sooner but at a smaller size compared to inland tadpoles, and more coastal tadpoles survived to metamorphosis. Chapter 3 used individual-based modeling to explore how density dependence and selection interact to affect evolution in complex life cycle organisms. Density dependence increased genetic variation across populations by reducing population size, and evolutionary rescue was most likely to occur when selection precedes density dependence. Chapter 4 used transcriptomics to explore the mechanisms that produce differences across inland and coastal populations. We identified 1,924 differentially expressed genes between coastal and inland frog populations. We found that differentially expressed genes encode diverse molecular functions including ionic and osmotic transporters and stress response pathways. This dissertation shows that coastal H. cinerea can become locally adapted to inhabit brackish habitats and explores several mechanisms that affect adaptive evolution to environmental change
Keywords: Anuran; Saltwater; Green treefrog--Physiology--North Carolina; Adaptation (Biology)--Environmental aspects; Evolutionary developmental biology